Medial Femoral Condyle Free Flap Reconstruction of Complex Foot and Ankle Pathology. Issue 4 (7th November 2019) - Stranix, John T.; Piper, Merisa L.; Azoury, Said C.; Kozak, Geoffrey; Ben-Amotz, Oded; Wapner, Keith L.; Levin, L. Scott
Background: Complex hindfoot pathology may benefit from vascularized bone flap reconstruction rather than traditional bone grafting techniques. Medial femoral condyle (MFC) flaps provide vascularized periosteum, skin, and corticocancellous bone. Methods: A retrospective, single-institution cohort study of consecutive MFC flaps performed for complicated hindfoot reconstruction between 2013 and 2019 was reviewed. Radiologic follow-up assessed osseous union and clinical outcomes were evaluated with the American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score. Thirty MFC flaps were performed in 28 patients for complex hindfoot pathology. Twenty-seven flaps had adequate clinical and radiographic follow-up (mean 15.8 months). Results: The majority presented with avascular necrosis (83%) and failed prior operations (67%, mean 3.1). Most hindfoot procedures involved arthrodesis (n = 24, 80%); tibiotalocalcaneal (n = 11) and talonavicular (n = 7) most frequently. Mean osseous flap volume was 10.3 cm 3 (range 1.7-18.4 cm 3 ); one flap required takeback for venous congestion but no total flap losses occurred. Primary osseous union was initially achieved in 20 patients (74%, mean 217 days). Six flaps developed interface nonunion; 5 underwent revision arthrodesis and ultimately achieved union in 24/27 flaps (89%, mean 271 days). Risk factors for nonunion were body mass index (BMI) >30 ( P = .017) and prior arthrodesis ( P = .042). Mean AOFAS hindfoot scores increased significantly from 52.3 preoperatively to 70.7 postoperatively ( P < .001). Subscore analysis demonstrated significant improvement in postoperative pain scores from 14.2 to 27.3 out of 40 ( P < .001). Conclusion: The MFC free flap provided vascularized bone for complicated foot and ankle reconstruction with relatively low donor site morbidity, promising osseous union results, and improved functional outcomes. Level of Evidence: Level IV, retrospective case series.